Clostridium difficile Biofilm: Remodeling Metabolism and Cell Surface to Build a Sparse and Heterogeneously Aggregated Architecture - Poquet, Isabelle; Saujet, Laure; Canette, Alexis; Monot, Marc; Mihajlovic, Jovanna; Ghigo, Jean-Marc; Soutourina, Olga; Briandet, Romain; Martin-Verstraete, Isabelle; Dupuy, Bruno (Frontiers in Microbiology, 2018)
Clostridium difficile is an opportunistic entero-pathogen causing post-antibiotic and nosocomial diarrhea upon microbiota dysbiosis. Although biofilms could contribute to colonization, little is known about their development and physiology. Strain 630erm is able to form, in continuous-flow micro-fermentors, macro-colonies and submersed biofilms loosely adhesive to glass. According to gene expression data, in biofilm/planktonic cells, central metabolism is active and fuels fatty acid biosynthesis rather than fermentations. Consistently, succinate is consumed and butyrate production is reduced. Toxin A expression, which is coordinate to metabolism, is down-regulated, while surface proteins, like adhesins and the primary Type IV pili subunits, are over-expressed. C-di-GMP level is probably tightly controlled through the expression of both diguanylate cyclase-encoding genes, like dccA, and phosphodiesterase-encoding genes. The coordinate expression of genes controlled by c-di-GMP and encoding the putative surface adhesin CD2831 and the major Type IV pilin PilA1, suggests that c-di-GMP could be high in biofilm cells. A Bacillus subtilis SinR-like regulator, CD2214 and/or CD2215, another regulator co-encoded in the same operon as CD2214, control many genes differentially expressed in biofilm, and in particular dccA, CD2831 and pilA1 in a positive way. After growth in micro-titer plates and disruption, the biofilm is composed of robust aggregated structures where cells are embedded into a polymorphic material. The intact biofilm observed in situ displays a sparse, heterogeneous and high 3D architecture made of rods and micro-aggregates. The biofilm is denser in a mutant of both CD2214 and CD2215 genes, but it is not affected by the inactivation of neither CD2831 nor pilA1. dccA, when over-expressed, not only increases the biofilm but also triggers its architecture to become homogeneous and highly aggregated, in a way independent of CD2831 and barely dependent of pilA1. Cell micro-aggregation is shown to play a major role in biofilm formation and architecture. This thorough analysis of gene expression reprogramming and architecture remodelling in biofilm lays the foundation for a deeper understanding of this lifestyle and could lead to novel strategies to limit C. difficile spread.